DDX19A Promotes Metastasis of Cervical Squamous Cell Carcinoma by Inducing NOX1-Mediated ROS Production - Jiang, Yanhui; Wang, Baibin; Li, Yongliang; Shen, Jiahui; Wei, Yutao; Li, Hanjie; Chen, Shangqiu; Yang, Hua; Zeng, Famin; Liu, Changqing; Wang, Feng; He, Huanhuan; et al. (Frontiers in Oncology, 2021)
The major obstacle to treat cervical squamous cell carcinoma (CSCC) is the high prevalence of metastasis, which severely affects five-year survival rate and quality of life for cancer patients. The DEAD-box helicase family has been reported to be critical mediator in the development and metastasis of various cancers. DEAD-box helicase 19A (DDX19A) is a member of this family, however, its functional role in CSCC is unclear. In this study, bioinformatics analysis of clinical samples from public databases demonstrated that the expression of DDX19A was elevated in CSCC tissues and that high expression of DDX19A was positively correlated with metastasis and poor clinical outcome. Functionally, we found that DDX19A promoted CSCC cell migration and invasion in vitro and lung metastasis in vivo. Mechanistically, overexpression of DDX19A increased NOX1 expression, enhanced reactive oxygen species (ROS) production, and induced the migration and invasion of CSCC cells. Rescue experiments revealed that DDX19A-induced CSCC functional alteration was mediated by NOX1 and that DDX19A-induced CSCC cell metastasis was abrogated with the N-acetylcysteine (NAC) treatment. Our results demonstrated that DDX19A could promote CSCC metastasis by inducing NOX1-mediated ROS production and that blockage of NOX1/ROS axis might serve as a potential therapeutic option for patients with DDX19A-ovexpressed CSCC.